The prognostic effects of the geriatric nutritional risk index on elderly acute kidney injury patients in intensive care units - Liao, Dan; Deng, Yonghua; Li, Xinchun; Huang, Ju; Li, Jiayue; Pu, Ming; Zhang, Fenglian; Wang, Lijun (Frontiers in Medicine, 2023)
Introduction The geriatric nutritional risk index (GNRI), a nutritional screening tool specifically for the aging population, has been proven to be associated with worse outcomes in chronic kidney disease patients, especially in the hemodialysis population. However, the predictive validity of GNRI in critically ill elderly patients with acute kidney injury (AKI) is yet to be determined. This analysis sought to examine the prognostic effects of GNRI on elderly AKI patients in intensive care units (ICUs). Methods We collected elderly AKI patient-relevant data from the Medical Information Mart for Intensive Care III database. AKI was diagnosed and staged according to the “Kidney Disease Improving Global Outcomes” criteria. In the study, 1-year mortality was considered the primary outcome, whereas in-hospital, ICU, 28-day and 90-day mortality, and prolonged length of stay in ICU and hospital were selected as the secondary outcomes. Results In all, 3,501 elderly patients with AKI were selected for this study, with a 1-year mortality rate of 36.4%. We classified the study population into low (≤98) and high (>98) GNRI groups based on the best cutoff value. The incidence of endpoints was remarkably lower in patients with elevated GNRI (p < 0.001). When stratified by the AKI stage, patients with high GNRI at AKI stages 1, 2, and 3 had markedly lower 1-year mortality than those with low GNRI (all p < 0.05). The multivariable regression analysis identified the independent prognostic ability of GNRI on the research outcomes (all p < 0.05). Restricted cubic spline exhibited a linear correlation between GNRI and 1-year death (p for non-linearity = 0.434). The prognostic implication of GNRI on 1-year mortality was still significant in patients with the most subgroups. Conclusion In critically ill elderly patients with AKI, elevated GNRI upon admission was strongly correlated with a lower risk of unfavorable outcomes.